Bridging Cultures through Community Engagement: Evaluating An International Summer Camp Initiative in Higher Education - Yupika Maryansyah; Albet Maydiantoro; Sheren Dwi Oktaria; Fitriadi (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: International summer camps have become a vital form of social engagement in higher education, providing chances for cultural learning and global contact. However, a rigorous evaluation of participant perceptions is required to ensure program efficacy and sustainability.Objectives: This study seeks to investigate students' impressions of the FKIP Universitas Lampung Summer Camp 2025, with an emphasis on cultural experience, program satisfaction, and areas for development in a community-based educational setting.Methods: This study used a descriptive quantitative technique supported by qualitative data. A perception questionnaire with a Likert scale was provided to 17 participants, supplemented with open-ended responses to elicit deeper insights into their experiences.Result: With mean values ranging from 4.50 to 4.89, the results show a high degree of participant satisfaction, especially in cultural activities, social connections, and committee support. Strong social ties and significant cross-cultural learning were noted by the participants. On the other hand, insufficient interaction with local pupils (M = 2.61) and time management (M = 3.83) were found to be moderate issues. Negative categories typically had low mean scores, suggesting that people thought the program was safe, inclusive, and relevant.Conclusion: All things taken into account, the summer camp successfully served as a community engagement program that increased student experience and cross-cultural knowledge while emphasizing the need for better scheduling and more possibilities for local contact. In addition to benefiting international participants, the program provided sociocultural benefits for the local community by strengthening cultural promotion and encouraging collaboration between universities and local stakeholders.